IMPLEMENTASI PRINSIP-PRINSIP PEMERINTAHAN YANG BAIK DALAM PELAYANAN PUBLIK : STUDI KUALITATIF DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL - Anggraini, Mela; Usamah, M. Dai; Bakil, M Sulthan; Siagian, Sahat; Sembiring, Tamaulina Br. (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to analyze the implementation of good governance principles in public service at the Department of Population and Civil Registration. Principles such as transparency, accountability, responsiveness, and public participation are the main focus in evaluating the quality of population administration services. The research employs a qualitative approach with in-depth interviews, observations, and document analysis. Findings indicate that some principles have been well implemented, particularly in information provision and digital-based administration systems. However, challenges remain, such as limited public participation, uneven responsiveness among staff, and users’ low digital literacy. The study recommends strengthening participatory mechanisms, service-oriented human resource training, and enhancing inclusive information systems. Overall, the study highlights the importance of integrating good governance principles to promote more effective, equitable, and sustainable public service governance.